The Placebo Effect And Its Determinants In Fibromyalgia: Meta-analysis Of Randomised Controlled Trials - Xi Chen; Kun Zou; Nicola Whiteside; Aliya Sarmanova; Michael Doherty; Weiya Zhang; Natasya Abdullah (Springer Nature Switzerland AG, 2024)
Indexed by SCOPUS